2016
DOI: 10.1016/j.ijscr.2016.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Mesh expansion as the cause of bulging after abdominal wall hernia repair

Abstract: HighlightsSwelling of the abdominal wall after abdominal wall reconstruction can be caused by a recurrence or bulging of the mesh.CT-scan can be useful to distinguish between a true recurrence or bulging of the mesh.Bulging of a mesh can be caused by pore enlargement and expansion of the mesh.The distinction between a recurrence and bulging of the mesh is therapeutically irrelevant in symptomatic patients.Mesh characteristics should be considered when choosing a feasible and suitable mesh for abdominal wall re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…This can cause alterations in the mesh's linear dimensions . It was shown that mesh shrinkage or expansion is associated with the development of chronic pain and increased chance of the recurrent herniation . Moreover, mesh stiffening can lead to mechanical irritation of the surrounding tissues, thus provoking further excessive immune response…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can cause alterations in the mesh's linear dimensions . It was shown that mesh shrinkage or expansion is associated with the development of chronic pain and increased chance of the recurrent herniation . Moreover, mesh stiffening can lead to mechanical irritation of the surrounding tissues, thus provoking further excessive immune response…”
Section: Discussionmentioning
confidence: 99%
“…32 It was shown that mesh shrinkage or expansion is associated with the development of chronic pain and increased chance of the recurrent herniation. 33,34 Moreover, mesh stiffening can lead to mechanical irritation of the surrounding tissues, thus provoking further excessive immune response. 32 However, there is a lack of consensus regarding the mechanism of hernia repair mesh deterioration caused by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…This difference creates the feeling of foreign body sensation. 15 But the sensitivity will be over countered by the time postoperatively. In the present study, 10 patients experience the foreign body sensation post-operatively at 1 month follow up, 5 patients at 3 month follow up and only 2 patients at the end of 1 year follow up.…”
Section: Discussionmentioning
confidence: 99%
“…Int Surg J. 2019 Jan;6(1):[13][14][15][16] International Surgery Journal | January 2019 | Vol 6 | Issue 1 Page 16…”
mentioning
confidence: 99%
“…If the implant behaves much more rigid than the original soft tissue, it gives rise to tensile stresses that may tear the tissue surrounding, provoking pain and discomfort in the patient and increasing the risk of tissue damage (Paajanen and Hemunen, 2004). On the other hand, if the implant behaves much softer than the muscles replaced, it may lead to an hernia recurrence or the presence of "bulging" of the prothesis due to its lack of strength (Schoenmaeckers et al, 2010;Deerenberg et al, 2016).…”
Section: Introductionmentioning
confidence: 99%